The problem of free will - Tugendhat, Ernst (Estudios de Filosofía, 2006)
The problem of free will is not whether it exists or not, but what it consists of. According to a popular opinion, free will is being able to do what one wants. For example, I can now, if I want, raise my hand. Two observations can be made in relation to that opinion. First: that the action depends on my will is not freedom of will, but of action, Second: it has recently been shown in brain physiology that every time one wants to move his hand, this act of the will is anticipated a fraction of a second by a movement in the brain. But even if that were not so, we would have to assume that the act of the will is determined by psychological antecedents, ’the alternative being that the person produces the act of will magically from nothing.